Laryngeal chondrosarcoma - Ten years of experience - Oliveira,José Fernando dos Santos (2014)
INTRODUCTION: Laryngeal involvement by cartilaginous tumors is rare. However, although accounting for only 1% of laryngeal tumor pathology, they are the most frequently occurring non-epithelial neoplasms. The most probable location is the endolaryngeal surface of the cricoid cartilage. Their symptoms are variable, depending on the size and location, and may include hoarseness, stridor, and dyspnea. Treatment is based on surgical excision. Some centers take into account the degree of differentiation and whether it is a case of relapse when deciding to perform a radical resection. AIM: To evaluate this disease in a sample of the Portuguese population. METHODS: A review of the medical records from 2002 to 2012 by assessment of clinical processes was performed. Data on demographics, clinical treatments, and outcomes were collected. RESULTS: Six patients were included in the study. Five of them underwent total laryngectomy, and in one case, partial excision of the thyroid cartilage was performed. None of the patients had either metastases or tumor-related death. CONCLUSION: Laryngeal chondrosarcomas remain a rare disease of unknown etiology, with slow and insidious symptoms. The treatment is surgical, with favorable prognosis, and metastases rarely occur. The main concern regards their propensity to relapse.